Imagens da escola: significado de representações sociais e alunos de escolas públicas - PIMENTEL, Maria Olinda Silva de Sousa (Universidade Estadual de Campinas, 2018)
This paper intends to appreciate the discourse of the child and of the adolescent under the perspective of verifying the understanding they have of their real life condition, having thei everyday schol expeience as a point of reference. Its process is characterized as na effort for the understanding of meanings of children's and adolescents' social schemes in a public school in the municipality of Campinas through the decoding of drawings and texts connected to the content of interviews made with the participants in the research. The meanings of the schemes were outlined based on the relationship between the real experience (the real school) and the aimed one (the ideal school). The context of these schemes was established with the objective of discussing this population's citzenship status, a population which has been thrown to the rear end of the chain of power relationships in our society. The appreciation of the discourse of the child and the adolescent while political subjects has permitted the identification of the content of the social criticsm present in drawings, texts, and interviews.This paper's conclusion points to the fact that the analysed schemes gave relevant weight to the subjects' informal exchange of experiences in the school enviroment outside the classroom, establishing a discussion between this non-institutional space and the symbols representa tive of the institional power which showed the relativeness of the pedagogical importance of the institution.The social criticism present in this characterization of the school points to the necessity of the establishement of new relationships